A Moxifloxacin-based Regimen for the Treatment of Recurrent, Drug-sensitive Pulmonary Tuberculosis: An Open-label, Randomized, Controlled Trial. (27th February 2019) - Perumal, Rubeshan; Padayatchi, Nesri; Yende-Zuma, Nonhlanhla; Naidoo, Anushka; Govender, Dhineshree; Naidoo, Kogieleum
Abstract: Background: The substitution of moxifloxacin for ethambutol produced promising results for improved tuberculosis treatment outcomes. Methods: We conducted an open-label, randomized trial to test whether a moxifloxacin-containing treatment regimen was superior to the standard regimen for the treatment of recurrent tuberculosis. The primary and secondary outcomes were the sputum culture conversion rate at the end of 8 weeks and the proportion of participants with a favorable outcome, respectively. Results: We enrolled 196 participants; 69.9% were male and 70.4% were co-infected with human immunodeficiency virus (HIV). There was no significant difference between the study groups in the proportion of patients achieving culture conversion at the end of 8 weeks (83.0% [moxifloxacin] vs 78.5% [control]; P = .463); however, the median time to culture conversion was significantly shorter (6.0 weeks, interquartile range [IQR] 4.0–8.3) in the moxifloxacin group than the control group (7.9 weeks, IQR 4.0– 11.4; P = .018). A favorable end-of-treatment outcome was reported in 86 participants (87.8%) in the moxifloxacin group and 93 participants (94.9%) in the control group, for an adjusted absolute risk difference of −5.5 (95% confidence interval −13.8 to 2.8; P = .193) percentage points. There were significantly higher proportions of participants with Grade 3 or 4 adverse events (43.9% [43/98] vs 25.5% [25/98]; P = .01) and serious adverse events (27.6% [27/98] vs 12.2% [12/98]; P = .012) in the moxifloxacin group. Conclusions: The replacement of ethambutol with moxifloxacin did not significantly improve either culture conversion rates at the end of 8 weeks or treatment success, and was associated with a higher incidence of adverse events. Clinical Trials Registration: NCT02114684. Abstract : Replacing ethambutol with moxifloxacin for the treatment of recurrent tuberculosis improved neither culture conversion rates at the end of 8 weeks nor treatment success, compared with the standard regimen, and was associated with a higher incidence of adverse events.